Analysis of the potential of implementing methane-based carbon tax on food waste in Indonesia - Nafi’ah, Zahra Zuhrotun; Dinarjito, Agung (WIM Solusi Prima, 2024)
Indonesia is the largest producer of food waste in Southeast Asia. Food waste is a contributor to greenhouse gases, therefore there needs to be a mechanism to reduce food waste and one of them is through a methane-based carbon tax. This research aims to discuss whether there is potential for implementing a methane-based carbon tax on food waste in Indonesia. This research is a qualitative research approach systematic literature review (SLR) and using the PRISMA method. The literature used is publications published from 2020 to 2024. From the results of the literature review it emerged that there is potential for implementing a methane-based carbon tax as well as implementing a carbon tax on food waste as has been done abroad. It is hoped that this research can become a reference for formulating tax policies related to carbon tax so that it can reduce the impact of food waste which will damage the environment. The limitation of this research is that it has not examined the Government's readiness to implement a methane-based carbon tax.